OPTIMALISASI SKEMA BAGI HASIL SEBAGAI SOLUSI PERMASALAHAN PRINCIPAL-AGEN DALAM PEMBIAYAAN MUDHARABAH PADA PT. BANK SYARIAH CABANG MAKASSAR - musdalifah, musdalifah; Muchran, Muchran (Universitas Muhammadiyah Makassar, 2018)
This study aims to find out how to optimize the revenue sharing scheme so that it can be a Principal-Agent problem solution in mudharabah financing. This research was conducted at PT. Bank BNI Syariah Makassar Branch. This research uses qualitative descriptive analysis techniques. The type of data used is primary and secondary data. Primary data is obtained from the results of field research with direct interviews with the BNI Syariah Productive Funding Assistant in Makassar Branch. Secondary data is obtained from company documents and other sources related to research. The results of this study indicate that there are two Principal-Agent problems that occur in financing with mudharabah contracts, namely adverse selection and moral hazard. Determination of optimal profit sharing schemes, namely those that meet the utility of Islamic banks and customers, the problem of adverse selection and moral hazard that occurs in mudharabah financing can be minimized. Although mudharabah financing has a high risk, by optimizing the profit sharing scheme on mudharabah financing, the existing risks can be reduced and there will be an increase in the amount of mudharabah financing to Islamic banks.